A Case Study: Feasibility and economic analysis for advanced automation in spoke rim assembly for motorcycle towards sustainability - Wang, Chenqing; Abdul Rahman, Azrul Azwan; Seliger, Günther (Springer Berlin Heidelberg, 2012)
A full automated system for assembly of spoke rim for motorcycle is difficult to realize, rather more manual and hybrid system until now, because of tight joining tolerance, increased complexities during assembly operation and wide diversity of variants. Due to recent increasing trends in labour cost and sustainability aspect advanced automation become more and more necessary. An industrial case study which deals with different improvement concepts for an economical feasible and technical realizable advanced automation of a motorcycle spoke rim assembly line is conducted. This paper presents a comprehensive analysis of the current implementation, a systematic approach to design the advanced automation concepts and a sustainable evaluation method in selecting the most feasible and realizable concept that ensures profitability and continuity.